Cardiovascular physiology - Mohrman, David E.; Heller, Lois Jane (McGraw-Hill Education Medical, 2014)
Suitable for USMLE and exam review, this title helps you gain a fundamental knowledge of the basic operating principles of the intact cardiovascular system and how those principles apply to clinical medicine.